Analisis Program GOWA (Gucialit Organisasi wisata alam) sebagai Inspirasi Kegiatan Sosial Masyarakat Kertowono Kabupaten Lumajang - Ika Dewi (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2022)
Argotourism in Lumajang Regency is also a driving force in increasing the economy and growth of PAD regional income in Lumajang Regency. Lumajang Regency has a number of destinations, but of the 24 tourist destinations, many tourist destinations have not received serious attention and are often ignored. weak to management, under Maximize Lumajang tourism promotion and not supported, poor infrastructure makes Lumajang tourist attractions less attractive and minimal visitors. This is less than the maximum effect of PAD obtained from Lumajang Regency in managing the tourism industry. This type of research is a descriptive qualitative case study to determine the perceptions, participation and aspirations of the community, and an analysis of the GOWA (Gucialit Nature Tourism Organization) program. Bringing culture to life and presenting beautiful nature and sea to other people (tourists), is the foresight and intelligence of a regional leader. The community is proud because the leader respects the culture/customs of the local community as well as the community gets additional income from preserving the culture/habits. The government will get appreciation from the people regarding the attention given by a leader to preserve their culture/customs through tourism programs as well as the government getting additional local revenue (PAD) from taxes and levies entering the area of ​​tourist objects and attractions. This is called a win-win solution. The surrounding community also gets economic benefits, because they are involved as tour guides, parking guards and are given the freedom to sell at the Kertowono tea garden tourist location. People's income has increased with the existence of this Kertowono tea garden tour.